2017
DOI: 10.14434/sdh.v1i2.23327
|View full text |Cite
|
Sign up to set email alerts
|

Digital 3D reconstructed models A proposition for structuring visualisation workflows using semantic technologies for recommendations

Abstract: It is common for cultural heritage applications to use spatial and/or spectral data for documentation, analysis and visualization. Knowledge of data requirements coming from the cultural heritage application and technical alternatives to generate the required data, based on object characteristics and other influential factors, pave the way for the optimal selection of a recording technology. It is a collaborative process, requiring the knowledge of experts both from cultural heritage domains and from technical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…These objects have been characterized by different dimensions, shape, color, texture, resistance to negative environmental influences and other characteristics. It is important to document activities related to protection of cultural heritage with as much information as possible [3,4]. Renju et al introduced a 3D digitizing pipeline for cultural heritage by using 3D technology for recovering geometry and texture with high precision [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These objects have been characterized by different dimensions, shape, color, texture, resistance to negative environmental influences and other characteristics. It is important to document activities related to protection of cultural heritage with as much information as possible [3,4]. Renju et al introduced a 3D digitizing pipeline for cultural heritage by using 3D technology for recovering geometry and texture with high precision [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Analyzing the costs related to 3D digitization in cultural heritage, Niccolucci [7] presented the figures from some case-studies and showed that owing to technological advancements, the costs of 3D data acquisition had been constantly decreasing. Selection of 3D digitization method in the field of cultural heritage represents a big challenge, especially for persons who are not experts in the field of 3D digitization (conservators, art historians, archaeologists) [4]. The aim of this paper is to develop an expert system for the selection of the most suitable 3D digitization method for scanning of different individual cultural heritage objects.…”
Section: Introductionmentioning
confidence: 99%
“…The creation of a 3D model and the subsequent steps towards restoration is, as Wefers et al (Wefers et al, 2017) states, a multidisciplinary task. The detailed requirements are set by CH experts, but the task itself is often executed by technical experts.…”
Section: Required Knowledgementioning
confidence: 99%